Highly sensitive scanning of gene mutations: TaqMan probes as blocking agents - I. V. Botezatu; I. O. Panchuk; A. M. Stroganova; A. I. Senderovich; V. N. Kondratova; V. P. Shelepov; A. V. Liсhtenshtein (Успехи молекулярной онкологии, 2016)
DNA Melting Analysis is very effective in clinical DNA diagnostics: it is simple to perform, high throughput, labor-, time- and cost-effective and is implemented in the “closed tube” format minimizing the risk of samples cross-contamination. Although more sensitive than sequencing by Sanger (mutant allele detection limit is ~5 and ~15 % respectively), it, however, is inferior in this respect to some other, more laborious and expensive methods (in particular, ddPCR (digital droplet PCR)). Using the BRAF gene as a prototype, we developed the original version of the DNA melting analysis, based on the ability of TaqMan probes to hamper the primer extension reaction by Taq-polymerase. It is found that the weaker blocking effect on the mutant template, which is due to the mismatch in the probe-DNA heteroduplex, permits enriched amplification of the mutant allele and provides a significant (10-fold or more) increase in sensitivity of mutation scanning.